Pharmacology of Chloroquine: Potential Mechanism of Action against Coronavirus - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: Chloroquine and hydroxychloroquine are recently reported to be effective in treating SARS-CoV-2 illness. The pharmacological mechanisms of this clinical benefit are continued to be explored. Materials and Methods: Using molecular docking tools in this study the binding affinity of Chloroquine and hydroxychloroquine were tested against two key SARS-CoV-2 targets i.e., 1) surface glycoprotein (6VSB) involved in viral attachment and 2) main protease (6Y84) involved in viral replication. Results: Chloroquine and hydroxy- chloroquine showed very effective binding affinity against both the SARS-CoV-2 targets. While the binding affinity against main protease was higher, multiple binding sites were observed on the surface glycoprotein of SARS-CoV-2. Conclusion: Chloroquine and hydroxy- chloroquinehave the potential to prevent SARS-CoV-2 attachment, entry and replication by directly binding to SARS-CoV-2 surface glycoprotein and its main protease.
Keywords: Chloroquine; Hydroxychloroquine; Protease inhibitors; Coronavirus; Covid-19; Antiviral drugs; SARS-CoV-2; Viral entry